Exosome-based approaches in cancer along with unlocking new insights into regeneration of cancer-prone tissues - Mohsen Safaei; Seyedeh Somayeh Rajabi; Mahtab Tirgar; Najmeh Namdar; Mahsa Dalfardi; Farnia Mohammadifar; Arash Goodarzi; Ahmad Reza Farmani; Vahid Ramezani; Zahra Abpeikar (Regenerative Therapy)
Most eukaryotic cells secrete extracellular vesicles called exosomes, which are involved in intercellular communication. Exosomes play a role in tumor development and metastasis by transporting bioactive chemicals from cancerous cells to other cells in local and distant microenvironments. However, the potential of exosomes can be used by engineering them and considering different therapeutic approaches to overcome tumors. Exosomes are a promising drug delivery approach that can help decrease side effects from traditional treatments like radiation and chemotherapy by acting as targeted agents at the tumor site. The present review provides an overview of exosomes and various aspects of the role of exosomes in cancer development, which include these items: exosomes in cancer diagnosis, exosomes and drug delivery, exosomes and drug resistance, exosomal microRNAs and exosomes in tumor microenvironment, etc. Cancer stem cells release exosomes that nurture tumors, promoting unwanted growth and regeneration, and these types of exosomes should be inhibited. Ironically, exosomes from other cells, such as hepatocytes or mesenchymal stem cells (MSCs), are vital for healing organs like the liver and repairing gastric ulcers. Without proper treatment, this healing process can backfire, potentially leading to disease progression or even cancer. What can be found from various studies about the role of exosomes in the field of cancer is that exosomes act like a double-edged sword; on the other hand, natural exosomes in the body may play an important role in the process and progression of cancer, but by engineering exosomes, they can be directed towards target therapy and targeted delivery of drugs to tumor cells. By examining the role and application of exosomes in various mechanisms of cancer, it is possible to help treat this disease more efficiently and quickly in preclinical and clinical research.